Peran Orang Tua dalam Pengenalan Budaya Literasi untuk Meningkatkan Kecerdasan Bahasa Pada Anak Usia Dini 5-6 Tahun (PIAUD IAIN Kudus, 2019)
The role of parents in introducing literacy culture of early childhood can be seen from the efforts of parents at home. The family is the place where the character of the child is formed, introduce the child to read a book that suitable with his developmental age, invite the child to hear some stories and create conducive atmosphere for them. Literacy culture of early childhood is not only focus on reading and writing, but also involves communication process which are listening, children are able to think logically and critically, and the development of linguistic intelligence orally. Among the parents’ attempts to introduce literacy culture of early childhood are: (1) family library and playing; (2) library membership registering; (3) library tour; (4) story telling; (5) watching a foreign tv channel; and (6) field trip. stimulate the literacy culture of early childhood.